Application of the Principle of Due Process of Law regarding narcotics crimes - Pulukadang, Novarolina; Nur, Rafika; Sumiaty, Sumiaty (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
The principle of due process of law implies a great respect for Human Rights (HAM). Basically the ultimate goal of the criminal justice system is due process of law as a legal process that is fair and impartial, proper, and is a true judicial process, which has gone through existing mechanisms or procedures, so that substantive justice can be obtained. So that the formulation of the problem in this study is the application of the principles of due process of law related to narcotics crimes. The purpose of this research is to realize the application of due process of law related to narcotics crimes. The method used in this study is an empirical juridical method using a statutory approach and looking at phenomena that occur directly in the field